2018
DOI: 10.1155/2018/7697903
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties and Sensory Evaluation of Wheat-Purple Rice Biscuits Enriched with Green-Lipped Mussel Powder (Perna canaliculus) and Spices

Abstract: Biscuits are one of the most consumed bakery products eaten by everyone. Purple rice contains much higher levels of antioxidants, vitamins, and minerals such as iron and zinc compared to wheat. The aim of this work was to produce a protein-rich biscuit made from purple rice flour and defatted green-lipped mussel powder (Perna canaliculus) (0–20%) blended with ginger and galangal spices at 4% for each spice. The objective was to produce an inexpensive, balanced, healthy snack product containing increased levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
1
19
0
3
Order By: Relevance
“…Developing novel biscuits by supplementing refined wheat flour with purple rice flour enriched with defatted mussel powder has been investigated by Klunklin and Savage (). The biscuits hold high promise with regard to antioxidant compounds and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Developing novel biscuits by supplementing refined wheat flour with purple rice flour enriched with defatted mussel powder has been investigated by Klunklin and Savage (). The biscuits hold high promise with regard to antioxidant compounds and antioxidant activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, purple rice also contains very high dietary fiber levels (Das, Goud, & Das, ; Jang & Xu, ; Yawadio, Tanimori, & Morita, ). Earlier studies by Klunklin and Savage () have reported that purple rice flour is a good ingredient for making biscuits and also contains high levels of antioxidants.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations